2010
DOI: 10.1016/j.rvsc.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of canine parvovirus strains isolated from cats with feline panleukopenia

Abstract: Unlike the original canine parvovirus type 2 (CPV-2), CPV-2 variants have gained the ability to replicate in vivo in cats but there is limited information on the disease patterns induced by these variants in the feline host. During 2008, two distinct cases of parvoviral infection were diagnosed in our laboratories. A CPV-2a variant was identified in a 3-month-old Persian kitten displaying clinical sign of feline panleukopenia (FPL) (acute gastroenteritis and marked leukopenia) and oral ulcerations, that died e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 44 publications
3
70
0
5
Order By: Relevance
“…It was assumed they were not owned and therefore not vaccinated, because of their presence at an animal shelter and non‐neutered status. Non‐vaccinated animals were preferred because it has been previously demonstrated that previous vaccination with FPV may cross‐protect for CPV as well, 13,35 although the degree of protection this confers is uncertain 5,18,25,34 . Because the samples were obtained postmortem samples, the history and clinical health of the animals were unknown and therefore the assumption that they were all healthy, without neurological or gastrointestinal signs, may have been erroneous.…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed they were not owned and therefore not vaccinated, because of their presence at an animal shelter and non‐neutered status. Non‐vaccinated animals were preferred because it has been previously demonstrated that previous vaccination with FPV may cross‐protect for CPV as well, 13,35 although the degree of protection this confers is uncertain 5,18,25,34 . Because the samples were obtained postmortem samples, the history and clinical health of the animals were unknown and therefore the assumption that they were all healthy, without neurological or gastrointestinal signs, may have been erroneous.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the current study, the cat presented severe clinical signs and survived after 3 days of treatment. In contrast, another study 9 also detected the CPV 426 Glu variant in a kitten but without hemorrhagic diarrhea; instead, that kitten had normal white blood cell counts and had been administered multivalent vaccines against FPV and other pathogens. The CPV-2a variant with the 426 Glu variation has already been reported in cats, in Italy.…”
Section: Research-article2014mentioning
confidence: 91%
“…Although CPV-2 and its variants replicate both canine and feline cells in vitro, FPLV infects to feline cells in vitro but does not replicate in canine cells [22]. Subtypes of CPV-2 have been reported from Asian and European countries in the cat population [6,14,23].…”
Section: Introductionmentioning
confidence: 99%